Comparing fixed‐amount and progressive‐amount DRO Schedules for tic suppression in youth with chronic tic disorders. Issue 1 (13th October 2016) - Capriotti, Matthew R.; Turkel, Jennifer E.; Johnson, Rachel A.; Espil, Flint M.; Woods, Douglas W.
Abstract : Chronic tic disorders (CTDs) involve motor and/or vocal tics that often cause substantial distress and impairment. Differential reinforcement of other behavior (DRO) schedules of reinforcement produce robust, but incomplete, reductions in tic frequency in youth with CTDs; however, a more robust reduction may be needed to affect durable clinical change. Standard, fixed‐amount DRO schedules have not commonly yielded such reductions, so we evaluated a novel, progressive‐amount DRO schedule, based on its ability to facilitate sustained abstinence from functionally similar behaviors. Five youth with CTDs were exposed to periods of baseline, fixed‐amount DRO (DRO‐F), and progressive‐amount DRO (DRO‐P). Both DRO schedules produced decreases in tic rate and increases in intertic interval duration, but no systematic differences were seen between the two schedules on any dimension of tic occurrence. The DRO‐F schedule was generally preferred to the DRO‐P schedule. Possible procedural improvements and other future directions are discussed.